2017
DOI: 10.1002/poc.3751
|View full text |Cite
|
Sign up to set email alerts
|

Structures and thermochemistry of methyl ethyl sulfide and its hydroperoxides: HOOCH2SCH2CH3, CH3SCH(OOH)CH3, CH3SCH2CH2OOH, and radicals

Abstract: Hydroperoxides and the corresponding peroxy radicals are important intermediates during the partial oxidation of methyl ethyl sulfide (CH3SCH2CH3) in both atmospheric chemistry and in combustion. Structural parameters, internal rotor potentials, bond dissociation energies, and thermochemical properties (ΔHfo, So and Cp(T)) of 3 corresponding hydroperoxides CH2(OOH)SCH2CH3, CH3SCH(OOH)CH3, CH3SCH2CH2OOH of methyl ethyl sulfides, and the radicals formed via loss of a hydrogen atom are important to understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 58 publications
(119 reference statements)
0
6
0
Order By: Relevance
“…These compounds play an important role in atmospheric and combustion chemistry, mainly in the formation of aerosols, and elimination of sulfur compounds from crude oil or coal. 1,2 They are also known to participate in global warming, acid precipitation, and cloud formation. 3 The contribution to the atmospheric sulfur burden from natural sources, such as volcanoes, plant and animal decay, marine algae, inland bodies of water, soil, bacteria, and so on, is estimated to be 0.47−2.2 Tmol S year −1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds play an important role in atmospheric and combustion chemistry, mainly in the formation of aerosols, and elimination of sulfur compounds from crude oil or coal. 1,2 They are also known to participate in global warming, acid precipitation, and cloud formation. 3 The contribution to the atmospheric sulfur burden from natural sources, such as volcanoes, plant and animal decay, marine algae, inland bodies of water, soil, bacteria, and so on, is estimated to be 0.47−2.2 Tmol S year −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Volatile organosulfur compounds (VOSCs) have been the focus of significant attention in recent years because of their contribution to the atmospheric sulfur budget. These compounds play an important role in atmospheric and combustion chemistry, mainly in the formation of aerosols, and elimination of sulfur compounds from crude oil or coal. , They are also known to participate in global warming, acid precipitation, and cloud formation . The contribution to the atmospheric sulfur burden from natural sources, such as volcanoes, plant and animal decay, marine algae, inland bodies of water, soil, bacteria, and so on, is estimated to be 0.47–2.2 Tmol S year –1 . , Various models have been made to develop a global sulfur cycle, but all of them underestimate the significant amounts of biogenic sulfur needed to balance the global sulfur cycle .…”
Section: Introductionmentioning
confidence: 99%
“…The potential energy diagrams in Figure are based on CBS‐QB3 level potential energy calculations for each species. The enthalpies of formation for the peroxides, radicals, aldehydes, and ketones of MES are from our previous studies . Values for O 2 , OH, and HO 2 are from Ruscic .…”
Section: Results and Analysismentioning
confidence: 99%
“…Cao et al have reported on the initiation of CH 3 SCH 2 CH 3 oxidation by OH from three different carbon sites showing similar barriers but different routes and kinetics. Several studies by Song et al have reported on the thermochemical and structural properties of the stable molecules of MES and all of its proposed partial oxidation intermediates, along with the properties of their radicals formed after loss of a H atom from each carbon. This study is on the reaction system of CH 3 SCH 2 CH 2 • + O 2 ; it identifies the reaction pathways and kinetics of sulfuric hydrocarbon partial oxidation and combustion that are initiated by abstraction of a H atom from the methyl carbon site on the ethyl group.…”
Section: Introductionmentioning
confidence: 99%
“…The potential energy diagram in Figure 4 are based on the CBS-QB3 level potential energy calculations for each species. The enthalpies of formation for the peroxides, radicals, aldehydes and ketones of MES are from our previous work, [53,54] while those of O 2 , OH, HO 2 are from Ruscic et al [56] The total enthalpies of products for each reaction step in Figure 4 are calculated based on the difference between the CBS-QB3 total energies of the reactants and the products.…”
Section: Thermochemical and Kinetic Analysismentioning
confidence: 99%